ChemInform Abstract: Regioselective Synthesis of Quinazolinone‐/Phenanthridine‐Fused Heteropolycycles by Pd‐Catalyzed Direct Intramolecular Aerobic Oxidative C—H Amination from Aromatic Strained Amides. Issue 29 (29th June 2016) - Banerji, Biswadip; Bera, Suvankar; Chatterjee, Satadru; Killi, Sunil Kumar; Adhikary, Saswati
Abstract: Under the reaction conditions only linear fused isomers are obtained.